1999
DOI: 10.1021/bc990076o
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Circulating Lives of Single-Chain Fv Proteins Conjugated with Polyethylene Glycol:  A Comparison of Conjugation Chemistries and Compounds

Abstract: The utility of single-chain Fv proteins as therapeutic agents would be substantially broadened if the circulating lives of these minimal antigen-binding polypeptides were both prolonged and adjustable. Poly(ethylene glycol) (PEG) bioconjugate derivatives of the model single-chain Fv, CC49/218 sFv, were constructed using six different linker chemistries that selectively conjugate either primary amines or carboxylic acid groups. Activated PEG polymers with molecular weights of 2000, 5000, 10 000, 12 000, and 20 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
110
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(114 citation statements)
references
References 37 publications
3
110
1
Order By: Relevance
“…Nevertheless, we found a decrease in apparent affinity when comparing the binding properties of the PEGylated constructs with those of their unPEGylated equivalents. This is in contradiction to some earlier reports (Chapman et al, 1999;Lee et al, 1999;Chapman, 2002) but consistent with a more recent study (Yang et al, 2003). Earlier reports had suggested that PEGylated antibody fragments, which carry the PEG tail at a site where direct interference with the binding region is unlikely, retain full binding activity.…”
contrasting
confidence: 56%
See 2 more Smart Citations
“…Nevertheless, we found a decrease in apparent affinity when comparing the binding properties of the PEGylated constructs with those of their unPEGylated equivalents. This is in contradiction to some earlier reports (Chapman et al, 1999;Lee et al, 1999;Chapman, 2002) but consistent with a more recent study (Yang et al, 2003). Earlier reports had suggested that PEGylated antibody fragments, which carry the PEG tail at a site where direct interference with the binding region is unlikely, retain full binding activity.…”
contrasting
confidence: 56%
“…This nonimmunogenic polymer (Caliceti and Veronese, 2003) can increase the hydrodynamic radius of the conjugated protein to a huge extent, leading to significantly decreased renal clearance (Chapman et al, 1999;Lee et al, 1999;Batra et al, 2002;Chapman, 2002). Furthermore, it can act to shield protein sites from recognition by the immune system or serum proteases (Cunningham-Rundles et al, 1992;Tsutsumi et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 5-fold reduction in apparent affinity upon PEGylation of the antibody fragments was observed in the kinetic BIAcore measurements (Table 2) as well as in the equilibrium binding assays on SK-OV-3 tumor cells (Table 1). In earlier reports (69,71,72) it was stated that antibody conjugates with a PEG polymer attached at a single engineered cysteine distal to the antigen binding site retain full binding activity. In a more recent study (50), however, similar findings of reduced affinity as we have demonstrated here were also reported for other scFv fragments that were site-specifically conjugated with PEG polymers of different sizes.…”
Section: Constructmentioning
confidence: 99%
“…Amine-directed chemical polysialylation (see below) was successfully used to modify an anti-tumour Fab (Constantinou et al 2008), but the same process damaged an anti-tumour scFv which was resolved by site-specific modification (Constantinou et al 2009). Similarly, conjugation of larger polymer chains using amine-reactive conjugation of an anti-TAG-72 scFv was also found to be more detrimental on antibody activity than conjugation to carboxylic acid moieties using PEG-hydrazine chemistry (Lee et al 1999). Unfortunately, in the absence of structural information it is difficult to predict which residues may be important for bioactivity.…”
Section: Chemical Conjugationmentioning
confidence: 99%